2020
DOI: 10.3390/rs12183002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Chromatic Aberration and Its Influence on the Processing of Underwater Imagery

Abstract: The number of researchers utilising imagery for the 3D reconstruction of underwater natural (e.g., reefs) and man-made structures (e.g., shipwrecks) is increasing. Often, the same procedures and software solutions are used for processing the images as in-air without considering additional aberrations that can be caused by the change of the medium from air to water. For instance, several publications mention the presence of chromatic aberration (CA). The aim of this paper is to investigate CA effects in low-cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For example, Menna et al (2017) analysed the accuracy potential lost in underwater photogrammetry due to optical aberrations introduced by the underwater port. Chromatic aberrations have been addressed for high precision photogrammetry (Luhmann et al, 2006) and in underwater photogrammetry as well (Neyer et al, 2019;Helmholz and Lichti, 2020). An automatic detection and removal approach of blurred UAV images was developed by Sieberth et al (2016) to improve analysis and interpretation of the data, as well as the accuracy of the photogrammetric processing.…”
Section: Related Researchmentioning
confidence: 99%
“…For example, Menna et al (2017) analysed the accuracy potential lost in underwater photogrammetry due to optical aberrations introduced by the underwater port. Chromatic aberrations have been addressed for high precision photogrammetry (Luhmann et al, 2006) and in underwater photogrammetry as well (Neyer et al, 2019;Helmholz and Lichti, 2020). An automatic detection and removal approach of blurred UAV images was developed by Sieberth et al (2016) to improve analysis and interpretation of the data, as well as the accuracy of the photogrammetric processing.…”
Section: Related Researchmentioning
confidence: 99%
“…This is perhaps natural due to the high degree of barrel distortion found in EWA imagery that is associated with the fisheye effect. Large radial lens distortion, in excess of 100 % of the distance between principal point and image format corner, has been reported for EWA cameras (Helmholz and Lichti, 2020; Lichti et al., 2020). However, as pointed out by Miyamoto (1964), a fisheye lens is not “an extension of a wide‐angle lens”.…”
Section: Introductionmentioning
confidence: 95%
“…A selection of action cameras, panoramic systems and mobile phones are examined. In recent years, a number of authors have reported on the calibration of action cameras – GoPro cameras in particular – due to their increased ubiquity, compact and lightweight design as well as robustness (Balletti et al., 2014; Ballarin et al., 2015; Teo, 2015; Hastedt et al., 2016; Bernardina et al., 2017; Wierzbicki, 2018b; Helmholz and Lichti, 2020). Similarly, panoramic camera systems featuring multiple, integrated sensors have also received attention in terms of the geometric calibration, notably Ladybug systems (Bosch et al., 2015; Rau et al., 2016; Lichti et al., 2020) and the Panono system (Khoramshahi and Honkavaara, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As authors report in [8], underwater chromatic aberration is more dominant in the underwater environment, and therefore significantly affects accuracy. Experiments using low-cost cameras, in water and in air show that accuracy varies considerably.…”
mentioning
confidence: 98%